The Value of Menumbai Sialang Tradition in History Learning Contributes to Character Building - Syafiq, Amirul; Kartini, Vidya Putri; Sudrajat, Sudrajat; Romdania, Sri Supitri (Universitas Negeri Padang, 2023)
This study analyzes the traditional values of menumbai sialang to shape Pancasila students' character in high school. It uses a descriptive qualitative approach with Vygotsky's constructivist theory. Data collection includes non-participant observation, interviews, and documentation, analyzed through triangulation. Results: (1) Swearing sialang is an ancient local tradition representing trinity through a procession for collecting forest honey. (2) Values aligned with Pancasila student indicators: (1) Swearing sialang is an ancient local tradition still in the process of taking forest honey with certain rituals representing the trinity relationship. (2) some values align with the character indicators of Pancasila students, namely (a) having faith-fearing God Almighty, reflected in the traditional procession as an expression of gratitude for God's gifts. (b) Global diversity, reflected in the awareness of the Petalangan tribe on the importance of maintaining their local culture. (c) Gotong royong can be reflected in the collective procession of gathering sialang. (d) Independence and responsibility are reflected in the efforts of the Petalangan tribe, who strive to conserve all resources. (e) Critical thinking, reflected in establishing customary sanctions for violators to maintain the balance of nature. (f) Creative, reflected in the ability of the Petalangan tribe to design environmentally friendly traditional tools to support traditional processions. (3) Menumbai sialang values can be integrated into high school history lessons through contextual learning, field trips, and the involvement of traditional leaders.